Handcuffs and chain link : criminalizing the undocumented in America - Gonzalez O'Brien, Benjamin (Charlottesville : University of Virginia Press, 2018)
"Handcuffs and Chain Link enters the immigration debate by addressing one of its most controversial aspects: the criminalization both of extralegal immigration to the United States and of immigrants themselves in popular and political discourse. Looking at the factors that led up to criminalization, Benjamin Gonzalez O'Brien points to the alternative approach of the Immigration Reform and Control Act of 1986 and how its ultimate demise served to negatively reinforce the fictitious association of extralegal immigrants with criminality. Crucial to Gonzalez O'Brien's account thus is the concept of the critical policy failure--a piece of legislation that attempts a radically different approach to a major issue but has shortcomings that ultimately further entrench the approach it was designed to supplant. The IRCA was just such a piece of legislation. It highlighted the contributions of the undocumented and offered amnesty to some while attempting to stem the flow of extralegal immigration by holding employers accountable for hiring the undocumented. The failure of this effort at decriminalization prompted a return to criminalization with a vengeance, leading to the stalemate on immigration policy that persists to this day"--Publisher's description
Introduction : considering criminality -- From open borders to locked doors -- From the path less traveled to the path best known -- Immigrant criminality and public opinion -- Policy preferences and the undocumented threat -- Conclusion : criminalization and reform.
Includes bibliographical references (pages 161-171) and index.
Online resource; title from electronic title page (EbscoHost, viewed December 17, 2018).
JSTOR
Keywords: United States -- Emigration and immigration -- Government policy; United States -- Emigration and immigration -- Political aspects; Crime and race -- United States; Immigration enforcement -- United States; Noncitizens -- United States; Illegal immigration -- United States; Criminalité et race -- États-Unis.; Émigration et immigration -- Lois -- Application -- États-Unis.; Immigrants clandestins -- États-Unis.; Immigration clandestine -- États-Unis.; États-Unis -- Émigration et immigration -- Politique gouvernementale; États-Unis -- Émigration et immigration -- Aspect politique; SOCIAL SCIENCE -- Emigration & Immigration; Noncitizens; Illegal immigration; Crime and race; Emigration and immigration -- Government policy; Emigration and immigration -- Political aspects; Immigration enforcement; United States; Electronic book